(untitled) (Herald of Journalism, 2018)
The article says that Internet radio is one of the newest types of means of mass communication, which makes it possible to obtain information in novom format. This type of media is an additional source of news, music for the modern man and is very different from traditional media, as it has its own peculiarities of broadcasting, its specific audience and territory, but is a full-fledged mass medium. Traditional media, despite their familiarity and clarity can no longer provide an adequate level of efficiency required by modern man. Therefore, more and more people are turning to the Internet to obtain relevant and up to date information.